Society on the move, weaving territorial peace in Nariño - Ruano-Jiménez Alba Jakeline (Sociedad y Economía, 2019)
This article contributes to the recognition and analysis of the experience of social mobilization for peace in Co- lombia, taking as a case study the experience of mobilization in Nariño, Colombia. The review of archival infor- mation and documents from institutions and social organizations identifies particularities of the experience of social mobilization for peace in Nariño. The population, through different repertoires of action, has sought to defend and contribute to the fabric of peace, to process conflicts by means others than violence, to contribute to welfare, respect for human rights and social justice. The wide experience of social mobilization for the peace is a sample of the fortitude, the resistance and the leadership in favor of peace in the territory, becoming the main social input to advance in the complex task of what is called “the construction of territorial peace”.